1999
DOI: 10.1007/bf02749957
|View full text |Cite
|
Sign up to set email alerts
|

Structure and tribological property of B2-based approximants

Abstract: The present paper is concerned with a special group of approximants with B2 superstructures. In the first part, recent work on structural features of the B2 superstructure approximants is summarized. Experimental results obtained in AI-Cu-Mn and AI-Cu systems are presented, where a series of B2-based approximants are observed. These phases all have similar valence electron concentrations, in full support of the e/a-constant definition of approximants. Special emphasis is laid on the chemical twinning modes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…These structures can be described in terms of basic B2 (CsCl) type of cell with the ordering among transition metals and vacancy along the [111] direction. Dong et al [6] have carried out extensive investigations on the occurrence of B2 phase, which resulted in the realization that the valence electron concentration of the B2 phase is similar to that of a quasicrystal. The B2 phase and related VOPs were found to co-exist extensively with the quasicrystalline phases, particularly in Al-Cu-TM (Ni, Co, TM= transition metal) systems and they follow a well-defined orientation relationship [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…These structures can be described in terms of basic B2 (CsCl) type of cell with the ordering among transition metals and vacancy along the [111] direction. Dong et al [6] have carried out extensive investigations on the occurrence of B2 phase, which resulted in the realization that the valence electron concentration of the B2 phase is similar to that of a quasicrystal. The B2 phase and related VOPs were found to co-exist extensively with the quasicrystalline phases, particularly in Al-Cu-TM (Ni, Co, TM= transition metal) systems and they follow a well-defined orientation relationship [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…phase, no such modulations are observed. However, Dong et al [7] have designated this phase in Al-Cu-Mn system as τ2 phase and have shown a close structural relation with icosahedral and decagonal phases. (121) is 16°±1°.…”
Section: Resultsmentioning
confidence: 97%
“…For this class of approximants, it has been proposed that there is an electronic structural correspondence between quasicrystalline and crystalline structure. Dong et al [6,7] have extensively studied the e/a (valance electron per atom) constant line in the ternary phase diagram of Al-Cu-Fe, Al-Cu-Mn, Al -Cu-(Fe,Cr) [6,7]. For example, it has been shown for Al-Cu-Fe system that the monoclinic Al 13 Fe 4 , icosahedral phase Al 62.…”
Section: Introductionmentioning
confidence: 97%
“…The decagonal quasicrystals have some structural similarity with several well known stable crystalline structures, for example Al 13 Fe 4, Al 3 Ni, Al 3 Ni 2 and B2 phases. All the crystalline Al 3 Ni, Al 3 Ni 2 and B2 phases can exist along with decagonal near the temperature of the decagonal phase formation [189]. The fraction of decagonal phase (FDP) has been calculated by comparing the integrated intensities of the most intense XRD peak of the D phase.…”
Section: Decagonal Phasementioning
confidence: 99%